The Role of Mid-Ranged Universities in Knowledge Transfer in Central and Eastern Europe - Sustainable University Strategies in the Era of Post-Mass Education UDK 378. 4 : 001. 92 - Gal, Zoltan (Journal of Economic Development, Environment and People, 2012)
JEL Classification: I23, I28, I25, I21